2021
DOI: 10.1049/ell2.12351
|View full text |Cite
|
Sign up to set email alerts
|

Thermally reconfigurable helical shape memory alloy–based metamaterial

Abstract: This paper presents our investigation and experimental validation of a thermally reconfigurable shape memory alloy (SMA)-based metamaterial with the offered degree of freedom of SMA mechanical features. The metamaterial unit cell consists of a two-way helical SMA acting as the resonator element and a cartridge heater for controlling the excitation temperature of the helical SMA. Experimental results of electrical control of the cartridge heater's excitation temperature show that as the temperature increases fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Compared to the planar arrays in MAs, the employment of SMAs facilitates 3D, structurally reconfigurable and tunable MAs, capable of tuning the absorption in a relatively larger range. [ 77,78,80 ] Phon et al. demonstrated a reconfigurable MM comprising of helical SMA.…”
Section: Periodic Patterns For Tunable/reconfigurable Masmentioning
confidence: 99%
See 3 more Smart Citations
“…Compared to the planar arrays in MAs, the employment of SMAs facilitates 3D, structurally reconfigurable and tunable MAs, capable of tuning the absorption in a relatively larger range. [ 77,78,80 ] Phon et al. demonstrated a reconfigurable MM comprising of helical SMA.…”
Section: Periodic Patterns For Tunable/reconfigurable Masmentioning
confidence: 99%
“…[77,78,80] Phon et al demonstrated a reconfigurable MM comprising of helical SMA. [78] The experimental results showed that the function of MM could be switched from an MA with nearly perfect absorption (97.2%) to a reflector with high reflectivity (89.4%) at 7.13 GHz when temperature of the SMA increased from 25 to 92 °C. The mechanism was ascribed to the extended length of the helical SMA under high temperature.…”
Section: Shape-memory Materialsmentioning
confidence: 99%
See 2 more Smart Citations